2021
DOI: 10.3390/ijms222111372
|View full text |Cite
|
Sign up to set email alerts
|

Post-Stroke Timing of ECM Hydrogel Implantation Affects Biodegradation and Tissue Restoration

Abstract: Extracellular matrix (ECM) hydrogel promotes tissue regeneration in lesion cavities after stroke. However, a bioscaffold’s regenerative potential needs to be considered in the context of the evolving pathological environment caused by a stroke. To evaluate this key issue in rats, ECM hydrogel was delivered to the lesion core/cavity at 7-, 14-, 28-, and 90-days post-stroke. Due to a lack of tissue cavitation 7-days post-stroke, implantation of ECM hydrogel did not achieve a sufficient volume and distribution to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…They found that the therapeutic window is dependent on a tissue cavity that allowed the bio-scaffold to be delivered. An optimal therapeutic time window for bio-scaffold-triggered regeneration of brain tissue and recovery occurred between 14 days and 28 days poststroke [ 71 ]. Silk has been used in humans for a long time [ 72 ].…”
Section: Hydrogels For Regeneration and Recoverymentioning
confidence: 99%
“…They found that the therapeutic window is dependent on a tissue cavity that allowed the bio-scaffold to be delivered. An optimal therapeutic time window for bio-scaffold-triggered regeneration of brain tissue and recovery occurred between 14 days and 28 days poststroke [ 71 ]. Silk has been used in humans for a long time [ 72 ].…”
Section: Hydrogels For Regeneration and Recoverymentioning
confidence: 99%
“…Over the last one-decade, significant progress was made towards understanding the implantable therapeutic devices and its interaction with the human immune system [69,70]. Human immune cells play a significant role in successful implantation of these devices and their function in the body for an extended period [71][72][73][74]. In this regard, mouse or rat models play a significant role in understanding this process, even though it is not quite similar to the human immune system.…”
Section: Challenges Of Clinical Translation Of Implantable Devicesmentioning
confidence: 99%
“…Interestingly, the phenotype induced by exposure to ECM scaffolds appears functionally distinct from canonical anti-inflammatory phenotypes, suggesting the response is more nuanced and requires additional study [ 157 ]. Nonetheless, one aspect is clear: decellularized ECM in its native, structured form or as an injectable hydrogel is an effective scaffold for immunomodulation and tissue repair, including in the CNS [ 159 , 160 , 161 , 162 ].…”
Section: Biomaterials Strategies To Modulate Immune Cell Phenotypesmentioning
confidence: 99%